UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN NHT (NUMBERED HEAD TOGETHER) DI KELAS VIII SMP - Emiyanti Emiyanti; Hotnida Sinaga; Zuhriani Fitriah (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
The purpose of this study was to determine the increase in mathematical problem solving ability of students after the applied learning model NHT (Numbered Head Together) in the Class VIII A SMP Negeri 2 Muara Bungo. The research subject is class VIII A SMP Negeri 2 Muara Bungo totaling 35 students. The object of this research is to improve student math problem-solving skills through learning model NHT (Numbered Head Together) in class VIII A Negeri 2 Muara Bungo T.A 2019 / 2020. The research is a classroom action research. In this study consisted of two cycles, which at the end of each cycle is given problem-solving ability test to determine students' mathematical problem solving ability. The shape is a matter for each test description. The first procedure in this study is to test the ability of the start of the classes studied, in order to see the initial mathematical problem solving ability of students. Second, with learning model application NHT (Numbered Head Together) presenting cubes and blocks. Before the act is done beforehand be given an early test for the ability of the start and the initial difficulties of students. From its initial test results obtained showed that the value - average grade VIII /A is 48.57. After giving the action through learning model Numbered Head Together in the first cycle, value - average test problem-solving abilities I is 71.78 with the number of students who have reached a level of completeness of classical study as many as 26 people (74.27%). Meanwhile, after repair of the first cycle in the second cycle, value - average test problem solving ability II is 83.21 with the number of students who have reached a level of completeness of classical study of 31 people (88.55%). Based on the results of this study indicate that by applying the learning model Numbered Head Together on the subject of cubes and blocks in class VIII A Negeri 2 Muara Bungo can improve students' mathematical problem solving abilities. Where improvement is obtained after the second cycle is done.